PENGARUH PENGHARGAAN FINANSIAL, PELATIHAN PROFESIONAL, PENGAKUAN PROFESIONAL DAN PERTIMBANGAN PASAR TERHADAP MINAT MAHASISWA BERKARIER MENJADI AKUNTAN PUBLIK - Fadjar Harimurti, Elga Dwiky Jaya, Dewi Saptantinah Puji Astuti & (Universitas Slamet Riyadi, 2018)
The purpose of this research is to analyze the significance of the influence of financial awards, professional training professional recognition and consideration of students' career interests against the market into a public accounting on Accounting Student Faculty of Economics Sebelas Maret University Surakarta. This study used a survey method, the type of data the data used was qualitative and quantitative data, the source data used the primary data and secondary data. The population in this research is the entire student accounting faculty of economic Sebelas Maret University Surakarta year 2014 force that already attended courses auditing auditing I, II and the application of the accounting review. The number of samples in the study based on the number of questionnaires returned, that as many as 74 respondents. Technique of data analysis used the test of validity, reliability test, test the assumptions of classical, and multiple linear regression analysis, t-test, F-test and coefficient of determination. The research results obtained the conclusion that the financial award, professional training, professional recognition and consideration of influential market significantly to variable i.e. interest student career became public accounting in college students accounting faculty of economic Sebelas Maret University Surakarta.Keywords: financial, professional training, professional recognition, market considerations, interests of students